Immunogenicity and safety of a cell culture-derived inactivated quadrivalent influenza vaccine (NBP607-QIV): A randomized, double-blind, multi-center, phase III clinical trial in adults and elderly subjects. Issue 7 (3rd July 2017) - Choi, Won Suk; Noh, Ji Yun; Song, Joon Young; Cheong, Hee Jin; Wie, Seong-Heon; Lee, Jin Soo; Lee, Jacob; Kim, Shin-Woo; Jeong, Hye Won; Jung, Sook-In; Kim, Yeon-Sook; Woo, Heung Jeong; et al.
ABSTRACT: Background : The influenza B virus has two lineages; Yamagata and Victoria. The two lineages are antigenically distinct and it is difficult to expect cross-protection between the lineages. Actually, the mismatch between circulating influenza B viruses and vaccine strains has been occurred frequently. The cell-culture system for the production of influenza vaccine can contribute to improve vaccine strain selection and expand vaccine supplies. We investigated the immunogenicity and safety of cell culture-derived quadrivalent inactivated influenza vaccine (NBP607-QIV) in adults and elderly subjects. Methods : A randomized controlled phase III trial was undertaken in 10 university hospitals in the Republic of Korea (Clinical trial Number—NCT02467842). Adults (aged 19–59 years) and elderly subjects (aged ≥60 years) were randomly assigned in a 2:1:1 ratio to NBP607-QIV versus cell culture-based trivalent inactivated influenza vaccine-Yamagata (NBP607-Y) and cell culture-based trivalent inactivated influenza vaccine-Victoria (NBP607-V). Immunogenicity was assessed 3 weeks after vaccination by hemagglutination inhibition assay. Safety was assessed for 6 months post-vaccination: solicited adverse events (AEs) for 7 days, unsolicited AEs for 21 days and serious adverse events (SAEs) for 6 months. AEs were sub-classified as adverse drug reactions (ADRs) according to the causality. Results : A total of 1, 503 participants were randomly assigned to NBP607-QIV (n = 752), NBP607-Y (n = 373) and NBP607-V (n = 378). The seroconversion rates of NBP607-QIV were 52.4%, 51.2%, 43.7% and 55.8% against A/H1N1, A/H3N2, B/Yamagata and B/Victoria, respectively. Non-inferiority against shared strains and superiority against alternate-lineage B strains were demonstrated for NBP607-QIV vs. NBP607-Y and NBP607-V. A total of 730 reactions occurred in 324 (43.1%) subjects of NBP607-QIV group. Majority of ADRs was solicited (99.2%) and mild (90.3%) in intensity. In adults (aged 19–59 years), solicited local AEs were slightly more frequent in NBP607-QIV group than NBP607-Y or NBP607-V group (40.9%, 33.4% and 32.5%, respectively). One SAE was observed among NBP607-QIV group, which was considered to be unrelated to the study vaccine within 3 weeks of vaccination and no vaccine-related SAEs were reported up to 6 months after vaccination. Conclusions : NBP607-QIV is a safe, well-tolerated and immunogenic influenza vaccine in Korean adults and elderly subjects.